The effect of foot reflexology massage on delirium and sleep quality following cardiac surgery: A randomized clinical trial - Ahmad Fazlollah; Hosein Babatabar Darzi; Esmail Heidaranlu; Seyed Tayeb Moradian (Elsevier, 2021)
Background: Delirium is the most common neurologic disorder after cardiac surgery and affects both short and long-term outcomes. This study was conducted to evaluate the effect of foot reflexology massage on the incidence of delirium and sleep quality in patients undergoing cardiac surgery. Methods: In this randomized clinical trial, 60 patients who were candidates for CABG surgery were randomly assigned into two equal groups (n = 30); intervention and control groups. In the intervention group, foot reflexology massage was done on each foot for 15 min, for two consecutive days. Delirium observation screening scale, the Richard Campbell sleep questionnaire (RSCQ), and pain intensity using VAS were compared. Results: in the second postoperative day, delirium was observed in 8 (26.7 %) and 7 (23.3 %) of patients in the intervention and control groups, respectively (p > 0.05). The measured odds ratio for the effect of massage on delirium is 0.83 (95 %CI 0.71-2.69, p = 0.76). The difference in RSCQ scores was not significant between groups of intervention and control (68.32 ± 10.41 VS. 62.80 ± 11.86, P = 0.06). The pain intensity was lower in the intervention group (P < 0.001). Conclusion: Foot reflexology was not effective in reducing delirium and improving the sleep quality, but the pain intensity was decreased. It seems that the precise pathology and predicting model of delirium should be identified, and appropriate interventions should be planned accordingly.